Cross-Cultural Analysis of Theory of Mind Development in Children with Autism Spectrum Disorder, Down Syndrome, and Typical Development - Shojaeian, Nazila (Journal of Medical Health Research and Psychiatry, 2024)
This study aimed to investigate the development of Theory of Mind (ToM) in children with Autism Spectrum Disorder (ASD), Down syndrome, and typical development from Iran and Sweden. Participants between the ages of 6 to 12 were assessed using various ToM tasks. Additionally, the study explored the correlation between children's behavioral problems, as reported by teachers and parents, and their ToM performance. Furthermore, the influence of family socioeconomic status on children's ToM understanding was examined. The research revealed that cultural factors played a partial role in specific ToM tasks during childhood, but not across the entire ToM construct in the studied groups. Introduction: Theory of Mind (ToM) refers to the ability to understand and attribute mental states, such as beliefs, desires, and intentions, to oneself and others. It plays a crucial role in social interactions and is an essential aspect of cognitive development in children. This study aimed to explore the influence of cultural factors on ToM development in children with Autism Spectrum Disorder (ASD), Down syndrome, and typical development. Methodology: The participants consisted of 74 native speakers from Iran and 66 from Sweden, falling within the 6 to 12 age range. They were divided into three groups based on their developmental profiles: children with ASD, children with Down syndrome, and typically developing children. ToM tasks were administered to measure their ToM abilities across all orders of complexity. Results: The study found that cultural factors partially influenced specific ToM tasks that children developed during their childhood. However, this effect was not observed across the entire ToM construct for any of the studied groups. The findings suggest that cultural differences might impact certain aspects of ToM development, but they do not have a universal effect on ToM understanding in the studied populations. The results also revealed a strong correlation between children's behavioral problems, as reported by teachers, and their ToM performance. However, this correlation was not significant when considering parents' perspectives. This discrepancy highlights the importance of considering multiple informants when assessing children's behavior and social cognition. Furthermore, the study examined the relationship between family socioeconomic status and children's ToM understanding. Surprisingly, no clear link was found in any of the studied groups, suggesting that socioeconomic status may not be a determining factor in ToM development among these children. Conclusion: In conclusion, this cross-cultural analysis provides valuable insights into the development of ToM in children with Autism Spectrum Disorder, Down syndrome, and typical development from Iran and Sweden. Cultural factors were found to have a partial influence on specific ToM tasks developed during childhood, while family socioeconomic status did not appear to be significantly linked to ToM understanding in these groups. The study also underscores the importance of considering different perspectives when evaluating children's behavior and social cognition. Further research is warranted to explore other potential factors that may impact ToM development in diverse populations.